Peningkatan Kemampuan Menulis Paragraf Deduktif dan Induktif dengan Menggunakan Model Picture and Picture di Kelas X Program IPS SMA Negeri 1 Kepahiang - Damairul Fatmah; Suhartono Suhartono; Gumono Gumono (LP4MK STKIP PGRI Lubuklinggau, 2020)
The purpose of this study was to determine the increase in the ability to write deductive and inductive paragraphs in class X IPS 4 students of SMA Negeri 1 Kepahiang 2018/2019 academic year by using the learning model of the type of picture and picture. The research method used is the classroom action research method. This research was conducted in two cycles. Each cycle consists of four steps: planning, implementing, observing, and reflecting. Data collection techniques using test, observation, and documentation techniques. Data analysis techniques by analyzing test data, analyzing teacher and student observation data, analyzing learning documentation, and testing the action hypothesis. Test the validity of the data using triangulation of data sources. The application of the picture and picture type learning model can improve students' understanding and motivation in doing the steps of writing paragraphs so that students are able to write deductive and inductive paragraphs. An increase in the average value of the ability to write deductive and inductive paragraphs by 10.91 points from cycle 1 to cycle 2, namely the average value in cycle 1 of 66.12 increased to 77.03 in cycle 2. For that reason, the learning model of the picture and picture type can used by Indonesian teachers to provide motivation and understanding to students in developing paragraph writing skills.